RANCANG BANGUN SISTEM INFORMASI E-BOOKING PENYEWAAN MOBIL BERBASIS WEB MENGGUNAKAN PENDEKATAN OOAD - Fallahi, Muamar; Nurfalah, Ridan; Fauzia, Inka Syaifa; Tarigan, Samuel (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
The manual system employed by PT. ACM Mahadat—a car rental service company—resulted in significant operational issues, including irregular schedules, data recording errors, and slow service, which contrasted sharply with consumer expectations for efficient and secure services. This study aims to design and build a web-based car rental e-booking information system to simplify the reservation process and manage data in real-time. The chosen methodology is Object-Oriented Analysis and Design (OOAD), a systematic approach that concentrates on the concept of objects as the fundamental system elements. The design documentation utilizes Unified Modeling Language (UML) notation, including the Use Case Diagram (functional requirements), Activity Diagram (process flow), Sequence Diagram (object interactions), and Class Diagram (static system structure). The resulting system is designed to be modular and flexible, offering a user-friendly interface for customers to view, select, and book cars easily. It also helps the Admin manage booking and rental data more efficiently, and its core authentication features are validated through Black Box Testing. This implementation is expected to support the digitalization of PT. ACM Mahadat's business processes and enhance the company's competitiveness in the information technology era.